The main factors that influence early menopause: a bibliographic review (Research, Society and Development, 2022)
Menopause is defined as the transition between the reproductive period and the non-reproductive period and corresponds to the last menstrual cycle. In contrast, early ovarian failure (FOP) is characterized by these aspects, before the age of 40 years. The study was carried out to review the specialized literature on risk factors for early menopause and their implications for the quality of life of women with this condition. This research is a narrative review, in an asystematic way, searched in databases such as Scielo, Medline, Lilacs, Pubmed and Psycinfo, from August to December 2021. It was complemented with materials directed by experts in the field, resulting in a extensive development of specific topics or with the latest techniques. Therefore, the results showed smoking, infections, idiopathic factors, genetic mutations, surgeries, among others, as risk factors for early menopause. Therefore, studies on early menopause were of paramount importance, mainly because they occur in young women, given that early diagnosis protects against more serious complications, with the greatest contribution mentioned, risk factors and encouragement about them. to maintain a healthy lifestyle, bone and cardiovascular health under normal controls to prevent any risk factors listed, in addition to avoiding possible infertility.